Phenylethylene glycol-derived LpxC inhibitors with diverse Zn2+-binding groups. Issue 4 (25th January 2019) - Galster, Magdalena; Löppenberg, Marius; Galla, Fabian; Börgel, Frederik; Agoglitta, Oriana; Kirchmair, Johannes; Holl, Ralph
Abstract: The Zn 2+ -dependent bacterial deacetylase LpxC is a promising target for the development of novel antibiotics. Most of the known LpxC inhibitors carry a hydroxamate moiety as Zn 2+ -binding group. However, hydroxamic acids generally exhibit poor pharmacokinetic properties. ( S )- N -Hydroxy-2-{2-hydroxy-1-[4-(phenylethynyl)phenyl]ethoxy}acetamide (3 ) is a known phenylethylene glycol derivative potently inhibiting LpxC with a Ki of 66 nM. In vitro experiments have confirmed in silico predictions that the hydroxamate moiety of3 is indeed metabolically labile. In this study, several strategies were explored to replace the hydroxamate moiety by other Zn 2+ -binding groups while maintaining target activity. In total, 15 phenylethylene glycol derivatives with diverse Zn 2+ -binding groups like carboxylate, hydrazide, carboxamide, sulfonamide, vicinal diol, thiol, thioester, and hydroxypyridinone moieties were prepared in divergent syntheses. However, their biological evaluation revealed that the replacement of the hydroxamate moiety of3 by any of the investigated Zn 2+ -binding groups is detrimental for LpxC inhibitory and antibacterial activity. Graphical abstract: